PENGEMBANGAN INSTRUMEN PENILAIAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN PRODUKTIF DI SEKOLAH DASAR - Dita Destiana; Yudhie Suchyadi; Fitri Anjaswuri (Universitas Pakuan, 2020)
DEVELOPING ASSESSMENT INSTRUMENTS TO IMPROVE THE QUALITY OF PRODUCTIVE LEARNING IN BASIC SCHOOLSThis study aims to produce competency-based assessment instruments in terms of cognitive, affective and psychomotor aspects that are needed in learning subjects in elementary schools. This study uses a Research and Development (RD) approach. Data collection techniques were carried out by interview, test, observation and limited circle discussion. The population in this study were teachers in the Cluster 8 Teacher Working Group, North Bogor District. Data were collected using questionnaires, interviews, and documentation. The validity of the data was obtained through construct validity using expert judgment and respondent validation. The data were analyzed by using quantitative descriptive analysis. The results of this study show that in general the assessment system in the Cluster 8 Teacher Working Group in North Bogor District can be categorized as good, including: (1) The antecedents aspect (assessment planning) can be categorized as good. This is indicated by the average score based on the teacher's questionnaire of 2.93 from a maximum score of 4. (2) The aspects of transactions (assessment implementation) can be categorized as good. This is indicated by the average score obtained based on student questionnaires and teacher questionnaires of 3.11 from a maximum score of 4. (3) The outcomes aspect (follow-up) can be categorized as good. This is indicated by the average score acquisition based on student questionnaires and teacher questionnaires of 2.82 from a maximum score 4. The percentage of content / material validity of the instrument product is 93.45%, the percentage of the value of the validity of the instrument product design is 84.76%, very category. valid, the practicality percentage of the assessment instrument is very practical with an average value of 84.86%, the percentage of product practicality based on student responses is 82.74% with the practical category. This development research produces an instrument for assessing student learning outcomes in science learning that is valid and practical so that it can be used as a tool for evaluating or assessing student learning outcomes that is accurate in cognitive aspects. It is recommended for teachers to apply instrument products for assessment of student learning outcomes in each assessment process, such as during mid-semester and semester exams and other examinations periodically.